2014
DOI: 10.1590/1809-4503201400060008
|View full text |Cite
|
Sign up to set email alerts
|

The Porto Alegre paradox: social determinants and tuberculosis incidence

Abstract: Porto Alegre presents high incidence rates of bacilliferous pulmonary tuberculosis, which distribution through the neighborhoods of the city is associated with socioeconomic factors. The city's high rate is due to the extremely high incidence rates in its poorest neighborhoods. The authors raise hypotheses and suggest interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 7 publications
(7 reference statements)
2
23
0
2
Order By: Relevance
“…A study examining European countries indicated a negative prospective association between logged gross domestic product and TB rates [11]. Contrarily, a different study reported that the city of Porto Alegre exhibited a higher pulmonary TB incidence despite its higher gross national product compared with neighboring cities with a lower level of income [12]. Likewise, in the present study, the city of Istanbul was established to be the province both with the highest level of income and the highest incidence of TB.…”
Section: Discussionsupporting
confidence: 49%
“…A study examining European countries indicated a negative prospective association between logged gross domestic product and TB rates [11]. Contrarily, a different study reported that the city of Porto Alegre exhibited a higher pulmonary TB incidence despite its higher gross national product compared with neighboring cities with a lower level of income [12]. Likewise, in the present study, the city of Istanbul was established to be the province both with the highest level of income and the highest incidence of TB.…”
Section: Discussionsupporting
confidence: 49%
“…A number of spatial studies have associated higher incidence rates of TB with higher housing density, poorer living conditions and lower socioeconomic factors [6, 1618]. In the present study we evaluated the density of cases from the kernel density map and hypothesized that density, income and percentage literacy of the population could partly explain the differences observed.…”
Section: Discussionmentioning
confidence: 90%
“…Some determinants of this scenario is the permanence of structural problems, precarious life conditions and continuous harm to the environment. 7,8 Recent studies reinforce the assumption that there is a socioeconomic gradient associated with the occurrence and distribution of TB, considered as a public health issue 9,10 . An important indicator of inequity is the difficulty to access adequate and opportune treatment 11 .…”
Section: Introductionmentioning
confidence: 91%